Enhancing the efficiency and equity of the tax system in Israel - Röhn, Oliver (OECD, 2020)
Israel’s tax mix is reasonably growth- and employment-friendly. Nonetheless, tax reform is needed to foster an inclusive recovery from the COVID-19 crisis and help tackle Israel’s main economic and societal challenges of high poverty, including among those in work, and slow aggregate productivity growth. The earned income tax credit has been an effective tool to reduce poverty and increase employment among the low-skilled and could be further expanded. The business tax system provides large benefits that aim to incentivise companies to become more productive, but the existing design may create distortions. This preferential tax treatment should be reviewed with a view to better targeting the scheme to ensure net benefits to society. There is also scope to simplify the tax system by removing inefficient tax expenditures and better leverage Israel’s impressive technological capacity to further lower compliance costs and reduce tax evasion. Finally, excise taxes should be adjusted, including by taxing carbon more heavily, to improve environmental and health outcomes.
10.1787/2b311bcc-en
Keywords: Amtsdruckschrift; Graue Literatur; taxes; personal income taxes; business taxes; tax administration; environmental taxation; tax avoidance; transfers; tax evasion; subsidies; Israel; Economics